Prospective Anticancer Efficacy of Bioactive Compounds from Chicoreus ramosus (Linnaeus, 1758) - Priya, P.Kaviya; Subavathy, P.; Dominikal, A. Maria Antony (Asian Journal of Biological and Life Sciences)
Aim: For over three decades, marine creatures have been a rich source of novel chemical compounds that have accelerated the development of marine natural product chemistry. Among the marine organisms, molluscs are one of the most successful forms of beast life and they’ve conquered nearly every niche and live in all the abysses. In the present study, marine gastropod Chicoreus ramosus have been selected with a view to screen the bioactive compounds responsible for biological activities. Materials and Methods: The cytotoxic effects of the experimental organism were performed using an MTT assay on the HeLa cell line. The chance of cell viability was set up to be dropped by adding attention to the samples. Results: The result of GC-MS results showed 10 compounds responsible for antioxidant and anticancer activities The results of the present study revealed that Chicoreus ramosus showed potent cytotoxic activities against HeLa cell lines with IC50 values of218.60 µg/mL. Conclusion: Methanolic extract of Chicoreus ramosus yielded a pool of bioactive compounds which are responsible for anticancer activity. Thus, it may be helpful to the pharmacological technologist for the extraction of anticancer drugs in the near future.
Keywords: Anticancer activity; Chicoreus ramosus; Gc-Ms analysis; HeLa cell line